Prefabricated hybrid steel wall panels for mid-rise construction in seismic regions. (January 2020) - Mortazavi, M.; Sharafi, P.; Kildashti, K.; Samali, B.
Abstract: Light steel framing systems are increasingly used in a variety of low-rise buildings, while are gradually penetrating to the mid-rise residential construction. The increased demand for mid-rise light weight steel frames in recent years has resulted in various research activities being undertaken in order to enhance the performance of these systems in compliance with the increased demands of mid-rise construction. This paper investigates the performance of a hybrid wall panel system (HWPS) made of a hot-rolled steel panel and a cold-formed steel panel in seismic regions. The hot-rolled steel panel resists the shear force, while the gravity load is distributed proportionally between the hot-rolled and cold-formed panels. The research employs the results of an experimental program to investigate the performance of the proposed hybrid panel, and a numerical study on the seismic performance of a 4-storey building made by HWPS. A practical design procedure is suggested for the system according to relevant specifications, and the results are compared with those obtained from employing a fully hot-rolled steel frame (moment resisting frame) and then a fully CFS frame system. The structural performance and the construction cost of two systems are then compared. Highlights: A new prefabricated hybrid steel wall panel is proposed for mid-rise construction. Using experimental and numerical investigations the performance of the wall panel is studied. In a case study, the results are used for the design of a 6-story building in seismic regions. Results are compared with those for fully hot-rolled and fully cold formed wall designs.